Postoperative central venous pressure is associated with acute kidney injury in patients undergoing coronary artery bypass grafting - Li, Jiale; Wang, Ruiling; Wan, Jun; Zhu, Peng; Xiao, Zezhou; Wang, Xiaowu; Zheng, Shaoyi (Frontiers in Cardiovascular Medicine, 2022)
Objective The present study aimed to investigate the association of postoperative central venous pressure (CVP) with acute kidney injury (AKI) and mortality in patients undergoing coronary artery bypass grafting (CABG). Method Patients who underwent CABG in the MIMIC-III database were included and divided into two groups according to the optimal cutoff value of CVP for postoperative AKI determined by the receiver operating characteristic (ROC) curves. The association of CVP with AKI and mortality was determined by multivariate regression models. A 1:1 propensity score matching (PSM) was performed to balance the influence of potential confounding factors. Results A total of 3,564 patients were included and divided into High CVP group (CVP ≥ 10.9 mmHg) and Low CVP group (CVP < 10.9 mmHg) according to the ROC analysis. Patients in High CVP group presented with higher AKI incidence (420 (28.2%) vs. 349 (16.8), p < 0.001), in-hospital mortality (28 (1.9%) vs. 6 (0.3%), p < 0.001) and 4-year mortality (149 (15.8%) vs. 162 (11.1%), p = 0.001). Multivariate regression model showed that CVP was an independent risk factor for the postoperative AKI (OR: 1.071 (1.035, 1.109), p < 0.001), in-hospital mortality (OR: 1.187 (1.026, 1.373), p = 0.021) and 4-year mortality (HR: 1.049 (1.003, 1.096), p = 0.035). A CVP above 10.9 mmHg was significantly associated with about 50% higher risk of AKI (OR: 1.499 (1.231, 1.824), p < 0.001). After PSM, 1004 pairs of score-matched patients were generated. The multivariate logistic model showed that patients with CVP ≥ 10.9 mmHg had a significantly higher risk of AKI (OR: 1.600 (1.268, 2.018), p < 0.001) in the PSM subset. However, CVP, as a continuous or a dichotomic variable, was not independently associated with in-hospital mortality (OR: 1.202 (0.882, 1.637), p = 0.244; OR: 2.636 (0.399, 17.410), p = 0.314) and 4-year mortality (HR: 1.030 (0.974, 1.090), p = 0.297; HR: 1.262 (0.911, 1.749), p = 0.162) in the PSM dataset. Conclusion A mean CVP ≥ 10.9 mmHg within the first 24 h after CABG was independently associated with a higher risk of postoperative AKI.